Shape Optimization of 2D Elastic Structures Using Adaptne Grids - Gutkowski, W.; Zawidzka, J. (Engineering Transactions, 1995)
The paper deals with an effective adaptive method for 2D shape optimization of linear elastic structures. The design objective is to find the shape of the kinematically unconstrained boundary assuring minimum volume of the structural material with constraints imposed on equivalent stresses. The geometrical shape parameters are the design variables. The method is based on a special kind of finite element automatically adaptive grids. The original iterative algorithm for solving the nonlinear system of equations and inequalities arising from the Kuhn-Tucker conditions is presented. The proposed approach is successfully tested on two classical examples.